Zom-B bride - Shan, Darren (Shan, Darren. Zom-B (Series), 2015)
B Smith considers making a sacrifice far greater and more surreal than any she has conceived before when she is reunited with the killer clown, Mr. Dowling, who desperately wants B as his partner in crime.